Effect of single dose and double dose antenatal corticosteroids on respiratory distress syndrome among preterm babies - N., Shivtej; R., Prema; Naidu, Apoorva; B. S., Amrutha; Mehta, Vidhi B. (International Journal of Contemporary Pediatrics, 2018)
Background: Respiratory distress syndrome occurs primarily in premature infants. The increased risk of RDS is associated with lower gestational age. The length of gestation is the primary factor that influences the risk of RDS the risk for development of RDS increases with maternal diabetes, multiple births, cesarean delivery, precipitous delivery, asphyxia, cold stress, and a maternal history of previously affected infants. Antenatal corticosteroids (ACS) significantly reduced neonatal morbidity and mortality when administered to women with imminent preterm delivery Antenatal steroids accelerate development of type 1 and type 2 pneumocytes, leading to structural and biochemical changes that improve both lung mechanics (maximal lung volume, compliance) and gas exchange. Induction of type 2 pneumocytes increases surfactant production by inducing production of surfactant proteins and enzymes necessary for phospholipid synthesis. Alveolisation occurs rapidly as a result of the antenatal corticosteroids Antenatal corticosteroid is usually administered for fetal lung maturity and can be expected to induce negative maternal and fetal side-effects hence this study was conducted to know the beneficial effect of single dose antenatal corticosteroids verses double doses antenatal corticosteroids. The Objective of the present study was to observe the effect of single dose and double dose antenatal corticosteroids on respiratory distress syndrome in preterm babies born to less than 37 weeks of gestation admitted under department of pediatrics at Raja Rajeswari medical college Hospital, Kambipura, Bangalore. Methods: There were 55 babies born to mothers who received single dose of antenatal corticosteroids and delivered at 12hrs before receiving 2nd dose antenatal corticosteroids and 55 babies born to mothers who received double dose of antenatal corticosteroids. Once baby is born, they compared for the requirement of surfactant. Results: Multiple course of steroids significantly reduced Respiratory distress syndrome. Conclusions: It was concluded that there was significant reduction in RDS in babies whose mother received complete course of antenatal corticosteroids.